Hepatitis and community: Developing framework and roadmap for ending the epidemic by 2030 - Suraj Kapoor; Pundla Nagarjuna (Wolters Kluwer Medknow Publications, 2023)
Introduction: Hepatitis is a well-documented public health challenge globally taking a heavy toll on lives, communities, and health systems. However, hepatitis has been largely ignored as a health priority until recently and the action against hepatitis cannot wait any longer. Still, a simplified framework and roadmap that can be applied across the globe against hepatitis are lacking which is highlighted in the present study. Methodology: Secondary data from official government sites, press information, latest articles, newspapers, and the WHO website were extracted and discussed in the article. A simplified framework and roadmap that can be applied across the globe against hepatitis are highlighted with the discussion on important factors in the roadmap to achieve the Sustainable Development Goal aim of ending the epidemic of hepatitis by 2030. Results and Discussion: A Total of 19 articles/government/international websites were assessed. Present study highlights various screening models that can be applied in developing framework in ending epidemic.The present study also highlights a roadmap for the prevention of hepatitis at the community level by 2030. The study elaborates on the important factors that should be incorporated in ending the epidemic of hepatitis by 2030. Conclusion: There must be a proper strategy to increase community awareness and knowledge, as well as for using community partnerships to boost community engagement and penetration. Equity, intersectoral action, blood safety, harm reduction strategies, surveillance, injection safety, infection control, environment sanitation, research and training, and health education are some of the strategies suggested for the roadmap to combat hepatitis.